Atypical presentation of posterior reversible encephalopathy syndrome: Two cases - Nishant Kumar; Ranju Singh; Neha Sharma; Aruna Jain (Wolters Kluwer Medknow Publications, 2018)
Posterior reversible encephalopathy syndrome (PRES) is a clinico-neuroradiological entity, first described in 1996. It is commonly associated with systemic hypertension, intake of immunosuppressant drugs, sepsis and eclampsia and preeclampsia. Headache, alteration in consciousness, visual disturbances and seizures are common manifestations of PRES. Signs of pyramidal tract involvement and motor dysfunction are uncommon clinical findings. However, clinical presentation is not diagnostic. On neuroimaging, lesions are characteristically found in parieto occipital region of the brain due to vasogenic edema. We report two cases of PRES with atypical clinical presentation-one which was suggestive of neurocysticercosis and the other in which agitation and opisthotonic posture were predominant features.